Monitoring Cold-Region Water Cycles Using Remote Sensing Big Data - Hongyi Li; Xiaohua Hao; Youhua Ran; Pengfeng Xiao (Remote Sensing)
In recent years, under the backdrop of global warming and intensifying extreme climates, water cycle processes in cold regions have been undergoing profound changes [...]